Manufacture and testing of water-borne paints by using vinyl latex containing VeoVa10® monomer - Aznar, Alberto Carlos (2006)
Two different water-borne dispersions (latex) containing different amounts of vinyl acetate and a commercial vinyl ester monomer (VeoVa10) were evaluated by incorporating them in paint formulations for wall protection. Three paint formulations were prepared with different PVC values. The main properties such as hiding power, washability, tension of adhesion and elasticity were assessed. Changes in color, gloss and adhesion and the extension of chalking, checking, cracking and blistering were also evaluated in normal and accelerated weathering tests. The results indicate that both dispersions are suitable for wall protection (interior or exterior, permanent or temporary protection) and  they are compatible with the most common additives used in the Argentinean and Mercosur markets. The presence of VeoVa10 in the binder composition improves the water and UV resistance of the paint. A styrenic-acrylic latex, commonly used in the local marked, was used as comparative product.